Civil society and peace: The role of Muhammadiyah in GPH-MILF Conflict - Mahdi, Imam; Chusnul, Mariyah (Technium Social Sciences Journal, 2022)
In fact, civil society has a huge chance to have an impact on each of these goals as a conflict transformation agent. Including Muhammadiyah, a civil society organization that works to resolve the conflict between the Philippine government and the MILF by acting as a locomotive for peace This study seeks to provide light on Muhammadiyah's role in bringing about peace in Mindanao. utilizing qualitative techniques, including in-depth interviews, on-the-ground observations, and document tracing. This study aims to draw attention to the fact that civil society, like Muhammadiyah, has not always been able to play a significant role in promoting peace. As a moderate Islamic organization, Muhammadiyah's main office is still not fully capable of visibly converting itself when it becomes an agent of peace.